Foveal Pit Morphology Evaluation during Optical Biometry Measurements using a Full-Eye-Length Swept-Source OCT Scan Biometer Prototype. Issue 6 (December 2015) - Bertelmann, Thomas; Blum, Marcus; Kunert, Kathleen; Haigis, Wolfgang; Messerschmidt-Roth, Anke; Peter, Monika; Buehren, Tobias; Sekundo, Walter
Purpose: To assess the scan quality of foveal pit morphology (FPM) and to quantify central retinal thickness (CRT) during routine optical biometry measurements with a full-eye-length swept-source optical coherence tomography (SS-OCT) scan biometer prototype (IOLMaster700) and to compare these results with standard examinations using spectral-domain optical coherence tomography (SD-OCT) technique (Cirrus4000 SD-OCT). Methods: As part of a SS-OCT scan protocol to measure biometric parameters for intraocular lens power calculation, central horizontal 1 mm retinal B scans were taken from phakic (group I) and pseudophakic (group II) nonvitrectomized eyes. To evaluate FPM, macular scans of either examination technique were subjectively analyzed and compared. Repeated CRT measurements were performed to analyze repeatability and consistency of IOLMaster700 recordings. These results were compared with CRT evaluations using SD-OCT. Results: Overall, 146 eyes of 146 patients were included in this series. The subjective assessments of FPM are illustrated. Repeated CRT measurements (repeatability) with the IOLMaster700 disclosed an overall intraclass correlation of 0.57 (group I: 0.48; group II: 0.89). Overall coefficient of variation (accuracy) was calculated to be 12.43% (group I: 14.21%; group II: 5.66%). The comparison of CRT measurements between both devices showed significant differences in group I (p = 0.006). Conclusions: Compared with SD-OCT, resolution of the 1 mm retinal B scan of SS-OCT scan biometry was lower. However, advanced pathologic characteristics were clearly discernible. Repeatability and accuracy of CRT measurements were acceptable though lower than with the standard SD-OCT technique. The CRT differed significantly in eyes of particular interest (group I) between both devices. The new scan could provide useful information for subsequent patient examination and further treatment planning for cataract surgery.